Isolation, tolerance, bioaccumulation and plant growth promoting activities of selenium tolerant fungal isolates in vitro and in vivo - Vashisht, Akanksha (My University, 2018)
Due to increased human activities like crude oil refining, combustion and various human activities, industrial waste release a large amount of gases and wastes. Wastes include different types of metalloids like Cd, Pb, Se, Te and Sb. Among these metalloids, selenium is required by the body in trace amount. The larger concentration of selenium is harmful to humans and leads to various diseases. Nowadays most of the areas are affected by selenium contamination and produces harmful effects on animals and humans. The objective of the present work was to isolate fungi from seleniferous soil means rich in selenium concentration. Microbes undergo various mechanisms to detoxify the concentration of metal and metalloid by various processes like complexation, biosorption, reduction and metal-fungal interaction. Fungal isolates can be used for bioremediation process means removal of heavy metals by living organisms. The objective of present work was to exploit the fungal strains Fusarium equiseti and Pseudopestalotiopsis theae and checked their tolerance level at different concentrations of sodium selenite tolerance level at higher concentration of selenium and showed plant growth promoting activities like phosphate solubilization, IAA production, HCN production and siderophore production. Fungal isolates act as a plant growth promoting fungi and good biofertilizers for plant growth. Use of microorganisms as a PGPR (Plant Growth Promoting Activities) and removal of Se from contaminated areas was cheapest method.
Keywords: Selenium, Seleniferous region, Fungi, Tolerance, Bioaccumulation, Plant growth promotion, Fusarium equiseti, Pseudopestalotiaopsis theae